2013
DOI: 10.3389/fgene.2013.00100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal, ontogenetic, and genetic factors on lifespan of male and female progeny of Arvicola amphibius

Abstract: The water vole (Arvicola amphibius) in the forest-steppe of West Siberia is known to have wide fluctuations in abundance. These fluctuations are accompanied by changes in birth and death rates, sex-age structure of the population, and individual morphophysiological and behavioral characteristics of the animals. Survival of the animals depends on season, phase of population cycle, and sex. Based on the data of long-term captive breeding of water voles, the maximal lifespan of males was found to be 1188 days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…A litter of 4.5 young at 5 g/young is 22.5 g (Stoddart 1971;Nazarova 2013), easily accounting for the weight difference between females and males in summer. Many males also lost mass during the summer, due to the costs of searching and fighting for females (Frafjord 2016).…”
Section: Ethical Approvalmentioning
confidence: 99%
See 3 more Smart Citations
“…A litter of 4.5 young at 5 g/young is 22.5 g (Stoddart 1971;Nazarova 2013), easily accounting for the weight difference between females and males in summer. Many males also lost mass during the summer, due to the costs of searching and fighting for females (Frafjord 2016).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…Many males also lost mass during the summer, due to the costs of searching and fighting for females (Frafjord 2016). Females should theoretically be able to produce 3-4 litters during May-July (sensu Stoddart 1971;Nazarova 2013), but the demands of reproduction may have increased the risk of being predated. This fact alone could explain the modest population increase of maximum 3.5 times during the summer on Trolløya.…”
Section: Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations
“…Novoseltsev and Novoseltseva ( 2013 ) used mathematical approaches to assess the origin of stochasticity in Drosophila reproduction, in relation to life expectancy. To add to mathematical predictions, analysis of long-term captive breeding of water voles demonstrated that individuals who began breeding at an older age had a significantly longer lifespan and produced more offspring (Nazarova, 2013 ).…”
mentioning
confidence: 99%